1997
DOI: 10.1007/s002560050306
|View full text |Cite
|
Sign up to set email alerts
|

Gorham's disease of the radius: radiographic, scintigraphic, and MRI findings with pathologic correlation

Abstract: A rare case of Gorham's disease affecting the radius in a 46-year-old woman is presented. It was studied by plain radiography, MRI, and scintigraphy, including three-phase radionuclide bone scan and thallium scan. Three-phase bone scan demonstrated slightly decreased activity in the affected portion of the forearm in the early phase, but showed increased activity on the blood pool and delayed imaging. A thallium scan revealed no abnormalities. Histopathologic examination revealed osteoclastic activity and scar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 15 publications
3
48
0
7
Order By: Relevance
“…Gorham and Stout (1955) suggested that "osteoclastosis" was not necessary and Foult et al (1995) found that osteolysis was secondary to angiomatosis. In contrast, Spieth et al (1997) reported that there was a clear relationship between osteoclasts and this rare syndrome, and Möller et al (1999) found a large number of multi-nucleated osteoclasts with hyperactive resorptive function in their patients. In our case series, the osteoclast in areas of bone resorption was found in only five cases (7.5%), which suggested "osteoclastosis" may be not necessary in this entity.…”
Section: Discussionmentioning
confidence: 89%
“…Gorham and Stout (1955) suggested that "osteoclastosis" was not necessary and Foult et al (1995) found that osteolysis was secondary to angiomatosis. In contrast, Spieth et al (1997) reported that there was a clear relationship between osteoclasts and this rare syndrome, and Möller et al (1999) found a large number of multi-nucleated osteoclasts with hyperactive resorptive function in their patients. In our case series, the osteoclast in areas of bone resorption was found in only five cases (7.5%), which suggested "osteoclastosis" may be not necessary in this entity.…”
Section: Discussionmentioning
confidence: 89%
“…However, these results have been variable. 116 The reported MRI findings of Gorham's osteolysis have also been variable. T1-weighted-spin echo MRIs show uniformly low signal intensity in the involved bones, whereas an increased signal intensity generally is observed in T2-weighted-spin echo images.…”
Section: Investigationsmentioning
confidence: 99%
“…The pathological process is the replacement of normal bone by an aggressively expanding but non-neoplastic vascular tissue, 57,97,113,116 similar to a hemangioma or lymphangioma. Wildly proliferating neovascular tissue causes massive bone loss.…”
Section: Etiopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is still the preferred imaging technique to evaluate the extension of the disease regarding the sensitivity to detect the soft tissue involvement. [10] Spieth and all, [13] using three phase bone scintigraphy with 99mTc-labelled methylene disphophonate and thallium imaging, demonstrated slightly decreased activity in the arterial phase, slightly increased activity in the blood pool phase, and increased activity in the delayed phase with normal thallium activity. Thallium imaging was performed to exclude malignant or soft tissue tumours.…”
Section: Discussionmentioning
confidence: 99%